Extended in vivo transcriptomes of two ascoviruses with different tissue tropisms reveal alternative mechanisms for enhancing virus reproduction in hemolymph - Heba A. H. Zaghloul (Nature Portfolio, 2021)
Abstract Ascoviruses are large dsDNA viruses characterized by the extraordinary changes they induce in cellular pathogenesis and architecture whereby after nuclear lysis and extensive hypertrophy, each cell is cleaved into numerous vesicles for virion reproduction. However, the level of viral replication and transcription in vesicles compared to other host tissues remains uncertain. Therefore, we applied RNA-Sequencing to compare the temporal transcriptome of Spodoptera frugiperda ascovirus (SfAV) and Trichoplusia ni ascovirus (TnAV) at 7, 14, and 21 days post-infection (dpi). We found most transcription occurred in viral vesicles, not in initial tissues infected, a remarkably novel reproduction mechanism compared to all other viruses and most other intracellular pathogens. Specifically, the highest level of viral gene expression occurred in hemolymph, for TnAV at 7 dpi, and SfAV at 14 dpi. Moreover, we found that host immune genes were partially down-regulated in hemolymph, where most viral replication occurred in highly dense accumulations of vesicles.